Plasma-Surface Interactions Within Helicon Plasma Sources - Del Valle, Juan I.; Chang Diaz, Franklin R.; Granados, Víctor H. (Frontiers in Physics, 2022)
Helicon plasma sources do not require electrodes or grids directly immersed in the plasma, and also present an axial magnetic field confining the plasma discharge. These factors are believed to provide them with long operational lifetimes because of the reduced potential for surface etching. The physics of helicon waves, cylindrical magnetized plasmas, sheaths, and plasma-surface interactions are discussed in the context of this claim. Practical implementation aspects are also reviewed, along with relevant experimental results. It is shown that understanding the distribution of ion density within the source, the presence of induced potentials in its surfaces, and the physics of low-energy sputtering reactions is essential to properly model erosion phenomena within helicons, and consequently predict their performance in practical applications.